UNDERGRADUATE STUDENTS' INVOLVEMENT IN DIGITAL PATIENT-EDUCATION STRATEGY AMID COVID-19 PANDEMIC (Proceedings of the International Conference on Education, 2021)
The COVID-19 pandemic generated relevant challenges in educating future physicians and brought attention back to the vulnerability caused by non-communicable diseases (NCDs), such as cancer, emphysema, and cardiovascular affections. Due to the risk of the 2019 Coronavirus contagion, the patient-based education strategies were put on hold, as they were face-to-face. Also, there was an urgent need to develop strategies that used new technologies to offer efficient and fast medical content to the non-specialized public. To overcome this situation, we involved undergraduate students of medicine in developing scientific content and infographics about the prevention and early diagnosis of cancer for a mobile application. The objective of this study was to assess the learning impact generated by the creation of digital patient-education materials. Five medical students enrolled in the Pathophysiology of Respiratory System course at Tecnologico de Monterrey were recruited as participants in the educational strategy with weekly sessions for four months. The following pedagogical tools were used during the intervention: project-based learning, challenge-based learning, engagement, service learning, science outreach, design thinking, and mentoring. Ten infographics for the mobile application were created after this experience. Also, a qualitative and transversal analysis of the undergraduates' learning was implemented using a focus group session as an instrument to evaluate the mentioned strategy's impact. As a relevant finding, we observed a high level of engagement, improvement in communication skills, and ethical reflections among the students. After the app is completed, we plan to create a social startup to generate more content about NCDs to promote prevention and early diagnosis. Educational strategies involving medical undergraduates in social projects have two beneficial outcomes: the student internalizes significant knowledge and positively impacts society's health. This project aims to inspire educators to empower students to develop real-life solutions as part of their college activities.
Keywords: Educational innovation; medical education; patient-education strategy; digital technology development; pandemic adaptations; cancer education